Sampling procedures for inspection by variables. Part 1: Specification for single sampling plans indexed by acceptance quality limit (AQL) for lot-by-lot inspection for a single quality characteristic and a single AQL Part 1, (22nd August 2022) - British Standards Institution,
No abstract available